Pengaruh persepsi kualitas, sikap merek, dan preferensi merek terhadap niat pembelian pada minuman susu frisian flag di Surabaya - Febrina Prita Putriansari (STIE Perbanas Surabaya, 2018)
The purpose of this research is to determine the infulence of perceived quality, brand attitude and brand preference of the purchase intention frisian flag milk in Surabaya. The variables used in this research were perceived quality, brand attitude, brand preference and purchase intention. This research used judgement sampling technique in order to get samples. Structural Equation Modeling AMOS was used for the analysis technique in this research with 130 respondent. The results of this study proves that the perceived quality have a significant influence on brand attitudes but no significant influence on purchase intention. Brand attitudes have a significant influence on brand preference but have no significant influence on purchase intentions. Brand preference has no significant effect on purchase intention